POLICY FAILURE, POLICY-IMPLEMENTATION GAP AND POLICY SUPPORT PROGRAMS - Berse Shey Blandine,; Nga Koulle Brigitte Christelle, (PEOPLE: International Journal of Social Sciences, 2025)
There is an increasing awareness that policies do not succeed or fail on their own merits. Within complex messy systems, it is unclear how best to ensure effective policy design and implementation. However, rather than just let policies drift into full or even partial failure, governments are now beginning to take an interest in ways in which the policy process – especially the implementation phase – can be strengthened and supported. This article contributes to the debate in three ways: by unpicking the key factors behind policy failure; by exploring different approaches to policy support; and by identifying key messages for policy practitioners